PATIENT-CENTERED NURSING SUPPORT IN THE REHABILITATION OF INDIVIDUALS WITH BRONCHIAL ASTHMA (Eureka Journal of Health Sciences & Medical Innovation, 2025)
Bronchial asthma is a chronic inflammatory disease of the airways that significantly affects patients’ physical, psychological, and social well-being. Effective rehabilitation plays a crucial role in improving disease control, preventing exacerbations, and enhancing quality of life. Nursing support is a key component in organizing, implementing, and assessing rehabilitation processes for patients with bronchial asthma. This article highlights the importance of nursing care in asthma rehabilitation, focusing on patient education, monitoring, individualized care planning, and outcome assessment. Strengthening the role of nurses in rehabilitation contributes to improved clinical outcomes, better self-management skills, and long-term disease control.
Keywords: Bronchial asthma, nursing support, rehabilitation, patient education, quality of life, disease management.